Tururi palm fibrous material (Manicaria saccifera Gaertn.) characterization. Issue 4 (15th January 2016) - Monteiro, Amanda Sousa; Leonardi, Barbara; Savastano, Holmer; Baruque-Ramos, Julia
Abstract : Tururi ( Manicaria saccifera Gaertn.) is a non-woven sac, which protects the fruits of the Amazon Ubuçu palm tree. The aim of this study was to use fibers withdrawn from these sacs and from sac strips – in the natural condition and after discoloration – to determine tensile, weight and regain values; additionally, longitudinal and cross-sections were studied using optical microscopy and Fourier transform infrared spectroscopy (FTIR) was carried out. The tensile results of fibers withdrawn from the sacs were 10·5 ± 2% elongation, 18 ± 3·2 cN/tex (175 ± 31 MPa) tenacity and 3·4 ± 0·5 N/tex (33 ± 5 GPa) Young's modulus. These values, in addition to regain (12·0 ± 0·5%) and cross-microscopy, are compatible with those of other lignocellulosic fibers. The results related to the strips were 5·9 ± 1% elongation, 17·6 ± 7·8 MPa strength and 552 ± 288 MPa Young's modulus. There was no significant statistical variation between the tensile characteristics of the fibrous material in the natural condition and after discoloration. The determined weight value was 182 ± 18 g/m 2 . FTIR analysis confirmed the presence of cellulose, hemicellulose and lignin. Finally, considerations about sustainable extraction and technical applications (in handcrafts and composites) of tururi fibrous material were made, presenting its potential to be employed in products, such as utensils, furniture, flooring or construction.